Coupled geomechanical model for compositional reservoir simulation with the finite volume method and unstructured grids - Gomes, João Henrique Bessa (2019)
Traditional petroleum reservoir modeling normally uses a single constant parameter, formation compressibility, to account for the effect of addition or removal of fluid from porous media. This single parameter approach has been shown to inaccurately depict the structural evolution of the reservoir during injection or production of fluids, especially for stress-sensitive formations. The geomechanical effect on the reservoir is therefore a more complex phenomenon that has to be analyzed thoroughly. Reservoir production causes formation compaction, which will modify some of its properties, such as porosity and permeability, that are important parameters for the calculations of fluid flow through porous media. The main objective of this work is to develop a coupled solution between a compositional reservoir simulator and a geomechanical model and apply it to different oil recovery processes. The open-code simulator UTCOMP was used for the implementation of the geomechanical model and its coupling with the reservoir model. UTCOMP is an equation of state compositional reservoir simulator developed by the University of Texas at Austin. The discretization approach used for both the reservoir and the geomechanical models is the Element-based Finite Volume Method, that allows the use of unstructured grids for the representation of the physical domain. The implementation is validated through problems with analytical solution available on the literature. Once validated, the coupled simulator is applied for different cases hydrocarbon recovery processes to evaluate the differences in production results caused by the use of the coupled geomechanical model.